Tort Law, Risk, and Technological Innovation in England - Oliphant, Ken (McGill Law Journal / Revue de droit de McGill, 2014)
This paper considers the impact of technological innovation—and the risks arising from it—on the development of English tort law in the modern era, dating from around 1750. At a time when the old forms of action were losing their grip, unprecedented social changes resulted from the Industrial Revolution and the risks that it created. New mechanisms (insurance, regulation and social welfare) were introduced to control these risks and mitigate their effects. Tort law too was obliged to adapt, and its modern contours bear the mark of this history. However, fundamental questions about the proper function of tort law relative to alternative compensatory and regulatory mechanisms remain to be satisfactorily resolved.